Impelementation Digital Population Identity Application in Public Service at Tempurejo Sub District Jember Regency - Niko Tirta Prayuata; Ivana Septia Maharani (Penerbit Jurnal Indonesia, 2024)
This research is motivated by the phenomenon related to the implementation of the Population Identity Digital Application in Jember Regency. Where in Jember Regency the application of the Population Identity Digital Application is still uneven. Of the 31 sub-districts in Jember Regency, only 8 sub-districts can activate this application. One of them is Tempurejo District. This is because there is one employee who has an attachment to the Jember Regency Dispendukcapil so that Tempurejo District is the centre of activation of the Population Identity Digital Application between 2 sub-districts including; Ajung and Jenggawah. So the researcher aims to find out the description of the Implementation of the Population Identity Digital Application in Tempurejo District, Jember Regency. Qualitative methods were used by researchers in this study where qualitative approaches and models can better explore problems that arise from social phenomena of population services and. The results showed that the Tempurejo District Government was influenced by two factors. Among them; Communication Factors and Human Resources Aspects. In the Communication Factor, Tempurejo Sub-district has not conducted socialisation related to the Digital Identity Population application. In the HR factor, only one employee understands in conducting public services with the Digital Population Identity application. So that I as the author provide advice to the Jember district government to overcome these two factors. So that all sub-districts in Jember Regency can activate the Digita Population Identity Application and also the people of Jember Regency understand about the Digital Population Identity application.